2019
DOI: 10.37358/mp.19.1.5130
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Some Polyolefin-TiO2 Composites Evaluated by Molecular Spectroscopy

Abstract: The photochemical degradation of polyolefin-TiO2 composite films was investigated and described in relationship with the concentration of photocatalyst and after different exposure times. UV-Vis-NIR and IR spectra reveal the presence of various degradation products, which are in direct connection with the photodecomposition mechanism. Various ratios between the absorbance of some typical IR characteristic bands can lead to the evaluation of photocomposition of polyethylene and polypropylene composite films con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…8(a) top). 140 They observed that while pure polyolefin films did not exhibit any sign of oxidation, films with the photocatalyst began oxidizing almost immediately after the irradiation began. They detected strong carbonyl, lactone, or alcohol peaks in the IR spectrum, which continuously grew with prolonged irradiation.…”
Section: Photocatalytic Oxidative Degradation Of Polymers With Hetero...mentioning
confidence: 99%
“…8(a) top). 140 They observed that while pure polyolefin films did not exhibit any sign of oxidation, films with the photocatalyst began oxidizing almost immediately after the irradiation began. They detected strong carbonyl, lactone, or alcohol peaks in the IR spectrum, which continuously grew with prolonged irradiation.…”
Section: Photocatalytic Oxidative Degradation Of Polymers With Hetero...mentioning
confidence: 99%